The Relationship Between Parental Knowledge, Attitudes, and Preventive Efforts Toward the Risk of Diabetes Mellitus in Overweight and Obese Elementary School Children - Priyantika, Afifah; Farah, Fransiska (Fakultas Kedokteran Universitas Pelita Harapan, 2024)
Background: Childhood obesity is a growing public health problem globally, strongly linked to the early onset of type 2 diabetes mellitus (T2DM). In Indonesia, the prevalence of obesity in children aged 5–12 years has reached 9.2%, with higher rates in urban areas. Parental knowledge, attitudes, and preventive efforts are considered important determinants in shaping children’s lifestyle behaviors and may influence their risk of T2DM. Methods: This study employed a descriptive-analytic cross-sectional design at SDN Jelambar 08, including parents and students from grades 1 to 6. A purposive sampling method was used, resulting in 190 respondents. Independent variables were parental knowledge, attitudes, and preventive efforts, while dependent variables included risk of T2DM and overweight/obesity status. Data were collected using self-administered questionnaires for parents and anthropometric measurements for children. Data analysis was performed with SPSS, using descriptive statistics and chi-square tests. Results: The study showed that 63.7% of parents were aware of diabetes risk factors, 71.1% demonstrated good attitudes, and 74.2% reported preventive efforts. Of the 190 children, 29.5% were classified as overweight or obese. Chi-square tests revealed no statistically significant association between parental knowledge (p=0.911), attitudes (p=0.140), or preventive efforts (p=0.872) and children’s diabetes risk in the context of overweight and obesity. Conclusions: Parental knowledge, attitudes, and preventive efforts were not significantly related to the risk of diabetes mellitus in overweight and obese children. A multifactorial approach that combines parental education, school-based programs, and pediatric monitoring is needed to address childhood obesity and prevent diabetes onset.